Costs and competition in retailing - McClelland, Grigor (London : Macmillan : New York : St. Martin's P., 1966)
This book explains some of the basic pattern of retailing as a business, with millions of result oriented decisions by individual proprietors or managers.
includes index
Bibliography: p. 328.
ii 15/01/2019
Loans
Keywords: Retail trade